Implementasi Proyek Penguatan Profil Pelajar Pancasila (P5) dalam Meningkatkan Keterampilan Seni Kriya dan Nilai Karakter Siswa Sekolah Dasar (Studi Kasus di SDN Sukomulyo, Magelang) - Muhammad Khoir; E. Kus Eddy Sartono; Fery Muhamad Firdaus (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to examine the implementation of the Pancasila Student Profile Strengthening Project (P5) as part of improving Pancasila Education learning at SDN Sukomulyo, with an emphasis on craft art as a contextual medium for internalizing the noble values of Pancasila. The main focus of this research is directed toward the tangible contribution of P5 in improving the quality of value-based character education. This study used a qualitative approach with a case study design. Data collection techniques included participatory observation, in-depth interviews with teachers, the principal, and students, as well as documentation of the planning process up to the students’ final products. The research results show that P5 plays an important role in shaping students’ character through project-based learning that emphasizes the values of mutual cooperation, independence, responsibility, and social awareness. These values are concretely actualized in the practice of craft art, which not only trains fine motor skills and creativity but also serves as a medium for reflecting the values of Pancasila. SDN Sukomulyo responded to these challenges with collaborative strategies. This study highlights the importance of synergy between Civics subjects, art, and the P5 project in creating a learning environment that fosters 21st-century skills and students’ national character. These findings contribute to the development of a more contextual Pancasila Education learning model through craft art as a medium for strengthening values and expressing local culture at the elementary school level.